Estimation of Metal Foam Microstructure Parameters for Maximum Sound Absorption Coefficient in Specified Frequency Band Using Particle Swarm Optimisation - FALLAH MADVARI, Rohollah; NIKNAM SHARAK, Mohsen; JAHANDIDEH TEHRANI, Mahsa; ABBASI, Milad (Archives of Acoustics, 2022)
The study aims to estimate metal foam microstructure parameters for the maximum sound absorption coefficient (SAC) in the specified frequency band to obtain optimum metal foam fabrication. Lu’s theory model is utilised to calculate the SAC of metallic foams that refers to three morphological parameters: porosity, pore size, and pore opening. After Lu model validation, particle swarm optimisation (PSO) is used to optimise the parameters. The optimum values are obtained at frequencies 250 to 8000 Hz, porosity of 50 to 95%, a pore size of 0.1 to 4.5 mm, and pore opening of 0.07 to 0.98 mm. The results revealed that at frequencies above 1000 Hz, the absorption efficiency increases due to changes in the porosity, pore size, and pore opening values rather than the thickness. However, for frequencies below 2000 Hz, increasing the absorption efficiency is strongly correlated with an increase in foam thickness. The PSO is successfully used to find optimum absorption conditions, the reference for absorbent fabrication, on a frequency band 250 to 8000 Hz. The outcomes will provide an efficient tool and guideline for optimum estimation of acoustic absorbents.